Implementation of the PJBL Model in Increasing the Interest of Class I Students in Elementary Schools - Winda Eprilia; Muhammad Rizky (Yayasan Pendidikan Genlita Indonesia, 2024)
This research is motivated by the low interest of students in conventional learning applied by teachers. The research aims to implement a project-based learning model to increase the interest of Class I students at SD Negeri 008 Palembang which totals 32 students. This research method is a classroom action research carried out through 2 cycles, namely Cycle I and Cycle II. The data collection techniques in this study are (1) Observation of students' interests with indicators of interest, feelings of pleasure, and active participation in learning. (2) PJBL learning data collection techniques. The results of this study show that: (1) the implementation of learning using STEAM-based PJBL in thematic learning, especially Indonesian Language and SBdP, can increase student interest, namely in the first cycle by 67.78% and in the second cycle by 82.03%(2) The increase in student interest can be seen from the results of learning reflection with the percentage of student interest in the first cycle of 37.5% and the second cycle of 87.5%.